Broad Impact of Exchange Protein Directly Activated by cAMP 2 (EPAC2) on Respiratory Viral Infections - Eun-Jin Choi; Wenzhe Wu; Xiaoyan Cong; Ke Zhang; Jiaqi Luo; Sha Ye; Pingyuan Wang; Adarsh Suresh; Uneeb Mohammad Ullah; Jia Zhou; Xiaoyong Bao (Viruses, 2021)
The recently discovered exchange protein directly activated by cAMP (EPAC), compared with protein kinase A (PKA), is a fairly new family of cAMP effectors. Soon after the discovery, EPAC has shown its significance in many diseases including its emerging role in infectious diseases. In a recent study, we demonstrated that EPAC, but not PKA, is a promising therapeutic target to regulate respiratory syncytial virus (RSV) replication and its associated inflammation. In mammals, there are two isoforms of EPAC—EPAC1 and EPAC2. Unlike other viruses, including Middle East respiratory syndrome coronavirus (MERS-CoV) and Ebola virus, which use EPAC1 to regulate viral replication, RSV uses EPAC2 to control its replication and associated cytokine/chemokine responses. To determine whether EPAC2 protein has a broad impact on other respiratory viral infections, we used an EPAC2-specific inhibitor, MAY0132, to examine the functions of EPAC2 in human metapneumovirus (HMPV) and adenovirus (AdV) infections. HMPV is a negative-sense single-stranded RNA virus belonging to the family Pneumoviridae, which also includes RSV, while AdV is a double-stranded DNA virus. Treatment with an EPAC1-specific inhibitor was also included to investigate the impact of EPAC1 on these two viruses. We found that the replication of HMPV, AdV, and RSV and the viral-induced immune mediators are significantly impaired by MAY0132, while an EPAC1-specific inhibitor, CE3F4, does not impact or slightly impacts, demonstrating that EPAC2 could serve as a novel common therapeutic target to control these viruses, all of which do not have effective treatment and prevention strategies.